THE ULTRASOUND DIAGNOSTICS POTENTIAL OF THE SMALL PELVIS TUMORS IN CHILDREN - N. A. Maksimova; Yu. Yu. Kozel; M. G. Ilchenko; G. A. Mkrtchyan (Южно-Российский онкологический журнал, 2020)
Purpose of the study. To assess the potential of sonography in the diagnosis of pelvic tumors in children.Patients and methods. We retrospectively analyzed results of ultrasound examination of the small pelvis, abdominal cavity and retroperitoneal space in 110 children with pelvic cancer referred for examination and treatment to National Medical Research Centre for Oncology of the Ministry of Health of Russia, distinguishing the most significant ultrasound parameters regardless of the tumor histological structure. 69.1% of patients were diagnosed with germ cell tumors, including 72.4% with gonadal and 27.6% with extragonadal tumors, 85.8% with sacrococcygeal tumors, 9.5% — uterine and 4.7% — vaginal tumors. Rhabdomyosarcoma was detected in 25.4%, neuroblastoma in 4.5% and a primitive neuroectodermal tumor in 1%. Standard ultrasound examination was performed using scanners Philips IU22 (USA) and Logic 400 MD (GE, USA) with convex transducers (3.5–5.5 MHz) in grayscale, color Doppler and power Doppler modes.Results. The first stage of diagnostics showed that malignant pelvic tumors were characterized with an irregular shape registered in 97 (88.2%; p<0.0001), uneven, fuzzy contours — 94 (85.5%; p<0.0001), heterogeneous echostructure — 102 (92.7%; p<0.0001), in 70 people (63.6%; р=0.001) due to cystic inclusions, calcified inclusions were found in 37 (33.6%; p>0.05); tumor echodensity was reduced in 75 children (68.2%; р=0.001). Dopplerography in most patients — 100 (90.9%) — registered a hyperintense intratumoral blood flow, mainly of an arterial type, with maximum arterial velocities (MAV) ranging from 12.5 to 45 cm/s, average MAV = 30±2.7 cm/s. The specificity of the method was 86.3% (p=0.001), sensitivity 85.2% (p=0.011), accuracy 87.5% (p=0.014). Ultrasound monitoring was performed during treatment after each polychemotherapy cycle; we assessed changes in the size of tumors, their structure and neovascularization, allowing evaluation of the antitumor treatment effectiveness.Conclusion. A complex sonography is an important method in the primary diagnostics of pelvic tumors in children, as well as a priority method in antitumor treatment monitoring, which allows detection of the tumor extent and helps to avoid multiple radiation exposure of the growing child’s body.